Formulation and stability test of stick balm preparation from red lemongrass (cymbopogon nardus L.) essential oil as aromatherapy and muscle pain reliever - Lea Wilhelmina Labobar; MarissaAnggia Ibrahim (JURNAL LENTERA ILMIAH KESEHATAN, 2025)
Balm is a topical preparation commonly used to relieve muscle pain through a warming effect. The innovation of balm in stick form offers more prac tical and hygienic application. This study aimed to formulate a balm stick from lemongrass (Cymbopogon nardus L.) essential oil, evaluate its physical stability, and conduct a skin irritation test. This experimental study employed steam distil lation and melting methods for preparation. Three balm stick formulations were developed based on varying concentrations of lemongrass essential oil: FI (20%), FII (25%), and FIII (30%). Stability tests included organoleptic observation, ho mogeneity, pH measurement, spreadability, and skin irritation assessment. Results showed that all formulations maintained stable color, aroma, and form for up to one week of storage. All three formulations exhibited good homogeneity and pH values within the skin standard (pH 5). The spreadability test indicated good ad herence to the skin, and no irritation was observed before or after storage. In conclusion, variations in essential oil concentration can be successfully formulat ed into an aromatherapy balm stick for muscle pain relief. The concentration all variations did not affect the stability of the preparations, and all formulations passed the skin irritation test, supporting their use as topical aromatherapy and muscle pain relief products.